From responsiveness to responsibility? The government experience of three parties of left-wing Euroscepticism - Ozkardes Akif Cem (Luiss Guido Carli, 2022)
One of the significant impacts of the 2009 Eurozone crisis was party system change in the crisis-stricken countries, especially in Southern Europe. As a result, new parties emerged, some parties disappeared and demanding more responsive governments, relatively less stronger parties became contenders for offices; and in some cases, they became ruling parties for the first time. Throughout the economic crisis another phenomenon, the rise of party-based Euroscepticism has drawn considerable interest from both journalistic and academic accounts and it has been often associated with party system change. In this context, considering the 2009 Eurozone crisis as a turning point and focusing on political parties which have criticized the EU predominantly through economic lenses, this research concerns the question of how government participation and the constraints imposed by European integration affect the Euroscepticism of ruling parties which came to power for the first time. Theoretically grounded on Mair (2007) and (2009)’s distinctions between policy-scepticism and polity-scepticism; and responsible and responsive government, the investigated question is whether ruling parties with left-wing oriented Euroscepticism become more responsible and less Eurosceptic once they come into office. Moreover, drawing on Mair (2007), this research puts forward a new typology for the Euroscepticism of such parties. Using qualitative case study method and selecting the two South European cases (i.e., the Coalition of the Radical Left [SYRIZA] of Greece; and Five Star Movement [M5S] of Italy) and a non-EU Nordic control case (i.e., the Left-Green Movement [VG)] of Iceland), this work investigates the impact of government participation and the constraints imposed by European integration on the Euroscepticism of Southern European ruling parties in Greece and Italy. The analysis is especially based on the collected data through semi-structured interviews with MPs and party cadres between June 2019 and November 2019. The findings ...